2022
DOI: 10.5380/rf.v52i4.71978
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH MODELS FOR Araucaria angustifolia (BERTOL.) KUNTZE IN DIFFERENT ECOLOGICAL GRADIENTS IN THE STATE OF SANTA CATARINA

Abstract: The growth of one or more individuals in a forest is variable with the biotic and abiotic conditions of the environment. Therefore, the objective of this article was to obtain the age and growth estimates of Araucaria angustifolia, in different altitude gradients of occurrence of the species, and to identify the culmination points in the basal area. The study covered three areas with Araucaria Forest in Santa Catarina state, considering different altitudes of occurrence of the species. Non-destructive samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Instead, the PB site is at the lowest altitude (713 m), annual average of 21 °C, explaining the greater tree rate growth observed. Ricken et al (2022) also observed that in higher altitudes Araucaria angustifolia trees reached growth stagnation stage earlier. Furthermore, the lower jaboticaba tree density (40.6 trees ha -1 ) were probably partially responsible for the greater growth in PB compared to CH,CL,and VT sites,with 59.6,75.6,and 45.8 jaboticaba tree ha -1 , respectively (Danner et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Instead, the PB site is at the lowest altitude (713 m), annual average of 21 °C, explaining the greater tree rate growth observed. Ricken et al (2022) also observed that in higher altitudes Araucaria angustifolia trees reached growth stagnation stage earlier. Furthermore, the lower jaboticaba tree density (40.6 trees ha -1 ) were probably partially responsible for the greater growth in PB compared to CH,CL,and VT sites,with 59.6,75.6,and 45.8 jaboticaba tree ha -1 , respectively (Danner et al, 2010).…”
Section: Discussionmentioning
confidence: 61%
“…Our findings have several implications for conservation and management of this species. For example, the diametric growth of P. peruviana were slow compared than others Mixed Ombrofilous Forest species (Canetti et al, 2016;Ricken et al, 2022;Stepka et al, 2021), ranged from 0.27 cm year -1 in site CH to 0.37 cm year -1 in PB, which may imply less competitiveness with other species when establishing in the forest. We also observed that jaboticaba trees in CL did not reach diameters larger than 40 cm, different from what was observed in other three locations (see Figure 5), indicating that there may be a restriction factor in growth in this site.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Contrasting tree allometric relationships in mixtures compared with monocultures can also influence APAR. For a given tree diameter, the crown sizes (width, length, surface area, and leaf area), shapes, or heights of a given species can differ in mixtures compared with monocultures [37,[59][60][61][62]. These allometric differences can add to the effects of the vertical foliage distribution when it allows crowns to expand sideways at different levels in the canopy or upwards or downwards away from other species [59].…”
Section: Thinning Intensity Issuesmentioning
confidence: 99%